The Impact of Partnership Forms on the Improvement of Coffee Farmers’ Welfare - Agustin, Esther Sri Astuti Soeryaningrum; Offermans, Astrid; Arifin, Bustanul (The Indonesian Forestry Certification Cooperation, 2023)
This study examines the optimal partnership structure for impacting the well-being of coffee farmers. It is crucial to elucidate the variances in each business model within the context of collaborations involving coffee farmers, traders, and exporters along the coffee supply chain, and their subsequent effect on the welfare of coffee farmers within each specific partnership configuration. We employed a questionnaire to assess the influence of partnership models on the well-being of farmers. The survey was carried out in Central Aceh, known for Arabica coffee production, and Lampung, recognized for Robusta coffee cultivation. we find that farmers participating in globally certified partnership constellations score better on economic performance than farmers in local partnership constellations (both certified and conventional).